2022
DOI: 10.55519/jamc-04-10746
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Varices and Associated Factors in Cirrhotic Patients With Hepatitis C

Abstract: Background: Infection with hepatitis C virus is reported to have infected almost 71 million people worldwide. This study was done to assess the frequency and associated factors leading to oesophageal varices in patients presenting with hepatitis C related liver cirrhosis. Methods: A cross-sectional study was conducted at Patel Hospital, Karachi, Pakistan from 9th May to 5th October 2019. Patients of either gender having age >20 years presenting with HCV related liver cirrhosis, and Child Pugh class A, B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…The baseline characteristics of each article were analyzed and summarized (participants, study design, country of origin of refugees, and outcome) in Table 3 . Of the 30 studies, 29 were cross-sectional ( 14 16 , 29 54 ), while one record-based study was found ( 13 ). The study period ranged from 2005 to 2022, with 22 studies conducted among the refugee population and eight studies conducted among internally displaced population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline characteristics of each article were analyzed and summarized (participants, study design, country of origin of refugees, and outcome) in Table 3 . Of the 30 studies, 29 were cross-sectional ( 14 16 , 29 54 ), while one record-based study was found ( 13 ). The study period ranged from 2005 to 2022, with 22 studies conducted among the refugee population and eight studies conducted among internally displaced population.…”
Section: Resultsmentioning
confidence: 99%
“…The study period ranged from 2005 to 2022, with 22 studies conducted among the refugee population and eight studies conducted among internally displaced population. In terms of geographical distribution, the majority (12 out of 30) of the refugees originated from the African region ( 15 , 32 , 34 – 37 , 39 , 45 , 47 , 49 , 50 ), followed by the Eastern Mediterranean Region (eight out of 30) ( 16 , 29 31 , 33 , 52 54 ) and South-East Asian region of WHO member states (nine out of 30) ( 14 , 38 , 40 44 , 48 , 51 ). One study was multicountry research ( 13 ), where the refugee population included were from Africa, South, East and Central Asia, and the Pacific African countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The false negative may result due to the inability to detect low viral load into samples [3] or due to body defects to produce antibodies in immune suppressed patients and those with current HIV infection [4]. On the other hand, the false positive may result due to some interfering medications received by the patient such as immunoglobulin therapy [5], patients with rheumatoid arthritis [6], patients who recovered from a previous infection [7], or due to antibody cross reactivity of similar viral antigens [4]. Therefore, antibody-targeted serological tests cannot differentiate between active or past-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the cost, the diagnostic methods based on the detection of viral genomes into the samples are more effective and accurate than serological methods [7]. In particular, reverse transcription polymerase chain reaction (RT-PCR) methodologies are easy to be established into laboratories with high sensitivity, automation facility, and low risk of contamination whether during reactions preparation or post-operation chemical disposal [9].…”
Section: Introductionmentioning
confidence: 99%